Brain white matter abnormalities associated with copy number variants. Issue 1 (17th October 2019) - Vigdorovich, Nitzan; Ben‐Sira, Liat; Blumkin, Lubov; Precel, Ronit; Nezer, Ifat; Yosovich, Keren; Cross, Zachary; Vanderver, Adeline; Lev, Dorit; Lerman‐Sagie, Tally; Zerem, Ayelet
Abstract: White matter (WM) signal abnormalities are demonstrated in various neurodevelopmental disorders on brain magnetic resonance imaging (MRI). The pattern of WM abnormalities can aid in the diagnostic process. This study aims to characterize the WM changes found in microdeletion/microduplication syndromes. Thirteen patients with neurodevelopmental disorders due to copy number variations were collected from a cohort of children with evidence of WM abnormalities on brain MRI, in two medical centers. A pediatric neuroradiologist blindly interpreted the MRI scans. Clinical and genetic findings were retrospectively extracted from the medical records. WM changes included: multifocal (10/13) periventricular (12/13) and subcortical (5/13) signal abnormalities and WM volume loss (6/13). Dysgenesis of the corpus callosum was depicted in 12/13. The main clinical features were: global developmental delay (13/13), hypotonia (11/13), epilepsy (10/13), dysmorphic features (9/13), microcephaly (6/13), short stature (6/13), and systemic involvement (6/13). We showed that different chromosomal micro‐rearrangement syndromes share similar MRI patterns of nonspecific multifocal predominantly periventricular WM changes associated with corpus callosum dysgenesis with or without WM and gray matter loss. Hence, the association of these features in a patient evaluated for global developmental delay/intellectual disability suggests a chromosomal micro‐rearrangement syndrome, and a chromosomal microarray analysis should be performed.